Inter-organizational information systems and business management : theories for researchers - Vaidya, Kishor, 1967- (Hershey, PA : Business Science Reference, 2012)
'This book highlights the most influential organizational theories and their applications in inter-organizational information systems, providing theories that have been consistently tested and proven to be valid over time'--
Includes bibliographical references and index.
Keywords: Information technology -- Management; Management information systems; Communication in organizations; Interorganizational relations